Effect of legume management on forage production and residual effects on upland rice - Schulz, S.; Keatinge, J.D.H.; Wells, G.; Shrestha, R. (Wiley, 2000)
An experiment was conducted over the period 1995–96 in a warm‐temperate environment in Nepal to investigate the effect of cutting frequency on forage yields of three temperate legume species, grown during the winter season, and the residual treatment effects on a subsequent upland rice crop. The three species, Persian clover (Trifolium resupinatum), white clover (Trifolium repens) and vetch (Vicia benghalensis), proved to be well adapted to the winter growing conditions and produced cumulative forage yields between 6.8 t DM ha−1 (vetch) and 9.2 t DM ha−1 (Persian clover). Vetch grew vigorously throughout the winter months and provided reasonable forage yields between December and February, whereas the clovers provided green fodder up to July. These species may therefore make a substantial contribution to alleviating the severe shortage of quality feed during the winter months. Grain yields of the subsequent rice crop ranged from 3.6 to 7.3 t ha−1. Rice yields were greatly affected by the previous legume species and forage management practices. In general, the removal of legume forage greatly reduced the residual effect, and farmers will have to seek a compromise between maximizing green fodder production and the immediate beneficial residual effect of the legume crop on rice yield.